2017
DOI: 10.12720/sgce.6.1.54-60
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the C: N ratio on the composting rate

Abstract: Sewage sludge was composted with the addition of straw and sawdust to modify the C: N ratio of dry matter. The experiment was conducted in closed and insulated bioreactors, at four C: N ratios: 9.2, 12.1, 17.0 and 26.4. The following parameters were measured during the composting process: temperature inside the bioreactor, aeration rate, ammonia and carbon dioxide emissions from the bioreactor. The composting process lasted 25 days. Temperature was measured after the end of composting, up to day 33 of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It has also been reported that the loss of OM decreases the weight of the precomposted material and reduces the C/N ratio [46]. Therefore, the final values obtained from this process were suitable for the vermicomposting process [56].…”
Section: Organic Matter (Om) Total Organic Carbon (Toc) Total Nitromentioning
confidence: 85%
“…It has also been reported that the loss of OM decreases the weight of the precomposted material and reduces the C/N ratio [46]. Therefore, the final values obtained from this process were suitable for the vermicomposting process [56].…”
Section: Organic Matter (Om) Total Organic Carbon (Toc) Total Nitromentioning
confidence: 85%
“…The optimal C/N ratio in the composting process is considered to be 25/1 to 35/1 (Guo et al, 2012). If the C/N ratio is higher than optimal, the composting process is slowed down because the activity of microorganisms is reduced, and at a lower C/N ratio, ammonia and unpleasant odors are generated (Neugebauer et al, 2017). There is a possibility of a successful composting process even at values of C/N ratios that are lower than optimal, and the research of some authors is shown in table 1.…”
Section: Composting Process Factorsmentioning
confidence: 99%
“…Rice straw organic mulch contains N between 0.5 -0.8%, P between 0.07 -0.12%, K between 1.2 -1.7% (Desiana, 2013), and a C/N ratio of approximately < 15 after the decomposition process to increase plant growth (Neugebauer et al, 2017). According to Asmoro & Susanto (2016), the decomposition process of organic matter takes a long time, in presence of a starter/activator such as microbes.…”
Section: Effect Of Rice Straw Organic Mulch On Cocoa Seed Growthmentioning
confidence: 99%